Distribution of intraperitoneally administered deuterium-labeled water in aquaporin-4-knockout mouse brain after middle cerebral artery occlusion - Urushihata, Takuya; Takuwa, Hiroyuki; Takahashi, Manami; Kershaw, Jeff; Shibata, Sayaka; Nitta, Nobuhiro; Tachibana, Yasuhiko; Yasui, Masato; Higuchi, Makoto; Obata, Takayuki (Frontiers in Neuroscience, 2023)
As the movement of water in the brain is known to be involved in neural activity and various brain pathologies, the ability to assess water dynamics in the brain will be important for the understanding of brain function and the diagnosis and treatment of brain diseases. Aquaporin-4 (AQP4) is a membrane channel protein that is highly expressed in brain astrocytes and is important for the movement of water molecules in the brain. In this study, we investigated the contribution of AQP4 to brain water dynamics by administering deuterium-labeled water (D2O) intraperitoneally to wild-type and AQP4 knockout (AQP4-ko) mice that had undergone surgical occlusion of the middle cerebral artery. Water dynamics in the infarct region and on either side of the anterior cerebral artery (ACA) was monitored with proton-density-weighted imaging (PDWI) performed on a 7T animal MRI. D2O caused a negative signal change quickly after administration. The AQP4-ko mice showed a delay of the time-to-minimum in both contralateral and ipsilateral ACA region compared to wild-type mice. Also, only the AQP4-ko mice showed a delay of the time-to-minimum in the ipsilateral ACA region compared to the contralateral side. In only the wild-type mice, the signal minimum in the ipsilateral ACA region was higher than that in the contralateral ACA region. In the infarct region, the signal attenuation was slower for the AQP4-ko mice in comparison to the wild-type mice. These results suggest that AQP4 loss affects water dynamics in the ACA region not only in the infarct region. Dynamic PDWI after D2O administration may be a useful tool for showing the effects of AQP4 in vivo.